Student bibliographies: charting research skills over time. Issue 3 (8th August 2016) - Lantz, Catherine; Insua, Glenda Maria; Armstrong, Annie R.; Pho, Annie
Abstract : Purpose: The purpose of this study is to compare two bibliography assignments completed after one-shot library instruction to determine which research skills first-year students retain over the course of a semester. Design/methodology/approach: A rubric was developed for citation analysis of student-annotated bibliographies and final bibliographies. Each assignment was scored on a three-point scale, and four criteria were assessed: the quality of sources used, variety of sources used, quality of annotations (for first assignment only) and citation accuracy. Findings: Students scored highest on the quality of sources used in both assignments, although there was a statistically significant decline in overall scores from the first assignment to the second. Students had the most difficulty with writing annotations, followed closely by citation accuracy. Students primarily cited journal articles in their annotated bibliographies and reference sources in their final bibliographies. Website use increased notably from one assignment to the other. Originality/value: This research is unique in its analysis of two separate bibliography assignments completed by first-year students over the course of a semester. It is of interest to librarians teaching one-shot library instruction or any librarian interested in assessing the research skills of first-year students.